Adrenocortical Tumor In Children – Report of a Case - Mahmood, Mansoor; Akhtar, Nadeem; Ismail, Saqib; ., Sheema; Owiwii, Yazeed (International Journal of Pathology, 2018)
AbstractAdrenocortical carcinoma in childhood is a rare, potentially fatal disease.Adrenocortical carcinoma has a bimodal age distributionwith cases clustering in children under 6, and in adults 30–40years old. We are presenting a case of 2 years old girlwho presented with symptoms of virilization. She was operated for the adrenal mass. A diagnosis of adrenocortical carcinomawas rendered.